(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Anxiolytic drugs are used for the treatment of anxiety disorders and their related psychological and physical symptoms. Today's increase in anxiolytic drug resistance has resulted in serious health issues. Thus, there is an ever-increasing demand for the design and synthesis of newer drugs for treatment. The present work reports the synthesis of some derivatives of pyrazolyl thiazolino-4-one viz. 2-[3-(furan-2-yl)-5-substituted phenyl-4,5-dihydro-1H-pyrazole-1-yl]-1,3-thiazole-4(5H)-ones. Six derivatives have been synthesized and the chemical structures were confirmed by IR, H1-NMR, and 13C-NMR. All the compounds were subjected to toxicity studies and then evaluated for their anxiolytic activity using elevated plus maze apparatus on rats. LD50 was found to be 98.11 mg/Kg. An increase in the percentage of time spent and the number of entries in the open arm of the plus maze signals a good potential for minimizing anxiety in rats. All the results were statistically tested by one-way ANOVA followed by Dunnett’s test. Compound 2; 2-[3-(furan-2-yl)-5-(4-dimethylamino- phenyl)- 4,5-dihydro-1H-pyrazol-1-yl]-1,3-thiazol-4(5H)-one and Compound 5; 2-[3-(furan-2-yl)-5-(2-chlorophenyl)-4,5-dihydro-1H-pyrazol-1-yl]-1,3-thiazol-4(5H)-one have shown percentage preference to open arm as 15.11 and 14.17 seconds and average time spent in open arm as 45.33 and 42.50 seconds respectively and thus resulted in significant anxiolytic effect as compared to control. These compounds can serve as potential leads for the development of newer therapeutic agents for the treatment of anxiety.